2014
DOI: 10.1111/jar.12099
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Key Concerns of Irish Persons with Intellectual Disability

Abstract: Why we did the research In many countries, people with intellectual disability have difficulties doing things other people without disabilities do, for example to study, to get a job or to live independently. They also find that their rights are not respected under the Convention on the Rights of Persons with Disabilities (the Convention). We did this study to Learn what are the main issues for adults with intellectual disability in Ireland. Do research with people with intellectual disability. How we did the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 12 publications
5
48
0
1
Order By: Relevance
“…A small and declining proportion of persons with intellectual disabilities were in receipt of employment supports from services over the 5 year period despite employment being a major goal in government policy (Health Services Executive, ). The latter is in line with the aspirations of persons known to intellectual disability services in Ireland and the UK (Garcia et al, ) and growing evidence that employment results in a better quality of life (Beyer, Brown, Akandi, & Rapley, ). The recently published employment strategy for people with disabilities in Ireland recognizes that employment is also an important route into greater social inclusion, a better standard of living and greater independence and aims to double the numbers of persons with disabilities in employment within 10 years (Government of Ireland, ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A small and declining proportion of persons with intellectual disabilities were in receipt of employment supports from services over the 5 year period despite employment being a major goal in government policy (Health Services Executive, ). The latter is in line with the aspirations of persons known to intellectual disability services in Ireland and the UK (Garcia et al, ) and growing evidence that employment results in a better quality of life (Beyer, Brown, Akandi, & Rapley, ). The recently published employment strategy for people with disabilities in Ireland recognizes that employment is also an important route into greater social inclusion, a better standard of living and greater independence and aims to double the numbers of persons with disabilities in employment within 10 years (Government of Ireland, ).…”
Section: Discussionsupporting
confidence: 71%
“…Within Ireland, for example, a new policy for day services "envisages that all the supports available in communities will be mobilised so that people have the widest possible choices and options about how they live their lives and how they spend their time" (p. 3) (Health Services Executive, 2012). In particular, increased opportunities for paid employment are to be promoted, which is in line with the aspirations of people with intellectual disability whose views were obtained in a national survey (Garcia Iriarte, O'Brien, McConkey, Wolfe, & O'Doherty, 2014) and confirmed by the self-advocacy of groups throughout Ireland (Government of Ireland, 2015 ).…”
Section: Introductionmentioning
confidence: 74%
“…This issue is compounded in the Republic of Ireland as schools and care centres may be provided by the same organisation. Nonetheless, many young people with intellectual disabilities aspire to paid employment and to greater social inclusion in their communities (Garcia Iriarte, O'Brien, McConkey, Wolff, & O'Doherty, ; Miller, Cooper, Cook, & Petch, ). Moreover, people with severe and profound disabilities invariably were placed in care centres with few opportunities for further education, training as well as employment.…”
Section: Discussionmentioning
confidence: 99%
“…A significant gap that remains in the literature is the absence of the perspectives of people with ID of the management process, barriers, and strategies used to improve mealtime safety. Prior research has clearly demonstrated that it is both possible and valuable to gather the views of people with ID about their own life experiences and to involve them in the research process (e.g., Garcia Iriarte et al, ). For those whose expressive communication is more limited and whose severity of cognitive impairments preclude traditional methods of experience elicitation, observational research, and gathering information from a carer as a proxy is indicated.…”
Section: Discussionmentioning
confidence: 99%